Complete genome sequence of the saprophytic actinomycete Prescottella soli DSD51WT, closely related to the multi-host pathogen Prescottella (Rhodococcus) equi - Yerlikaya, Zeynep; Miranda-CasoLuengo, Raul; Gaora, Peadar O.; Meijer, Wim G. (Amer Soc Microbiology, 2024)
Prescottella soli strain DSD51W(T) is an aerobic, non-spore-forming, non-motile actinomycete isolated previously from soil collected from Kyoto Park, Japan, using a resuscitative technique. Here, we report the complete, circular genome sequence of P. soli DSD51W(T). We employed a hybrid approach using Illumina and Oxford Nanopore platforms.
Keywords: Rhodococcus; Prescottella; genome analysis